Analisis Penerapan Aktivitas Pengendalian SIA terhadap Kinerja Keuangan Dinas Kelautan dan Perikanan Sumatera Utara - Naibaho, Dameria; Simbolon, Bernadetta Anita Jerry; Ratna; Simanjuntak, Darmawati; Saragih, Agus Mariani (Jurnal Akuntansi, Keuangan dan Perpajakan, 2024)
This research aims to determine the application of control activities from the accounting information system at the North Sumatra Province Maritime and Fisheries Service with control activities according to the Committee of Sponsoring Organization (COSO). The data collected through interviews is primary data such as documents and sections involved in finance and implementation of information systems and control activities at the North Sumatra Province Maritime and Fisheries Service. The data collected was analyzed descriptively by comparing control activities at the North Sumatra Province Maritime and Fisheries Service with control activities according to COSO. The results obtained indicate that the control activities at the North Sumatra Province Maritime and Fisheries Service are in accordance with and fulfill the control activities according to COSO. Thus, the accounting information system at the North Sumatra Province Maritime and Fisheries Service is appropriate and running well with respect to financial performance. However, it is necessary to provide training to employees or honorary employees in the agency so that they can improve their skills and accuracy in working so that their performance is more effective in accordance with the procedures for operational activities in the North Sumatra Province Maritime and Fisheries Service. Abstrak Penelitian ini bertujuan untuk mengetahui penerapan aktivitas pengendalian dari sistem informasi akuntansi pada Dinas Kelautan dan Perikanan Provinsi Sumatera Utara dengan aktivitas pengendalian menurut Committee of Sponsoring Organization (COSO). Data yang dikumpulkan melalui wawancara merupakan data primer seperti dokumen dan bagian yang terlibat dalam keuangan dan penerapan sistem informasi serta aktivitas pengendalian pada Dinas Kelautan dan Perikanan Provinsi Sumatera Utara. Data yang dikumpulkan di analisis secara deskriptif dengan cara membandingkan aktivitas pengendalian pada Dinas Kelautan dan Perikanan Provinsi Sumatera Utara dengan aktivitas pengendalian menurut COSO. Hasil yang diperoleh menunjukkan bahwa aktivitas pengendalian pada Dinas Kelautan dan Perikanan Provinsi Sumatera Utara telah sesuai dan memenuhi aktivitas pengendalian menurut COSO, Dengan demikian bahwa sistem informasi akuntansi pada Dinas Kelautan dan Perikanan Provinsi Sumatera Utara telah sesuai dan berjalan dengan baik terhadap kinerja keuangan. Akan tetapi perlu diberikan pelatihan kepada para pegawai atau honorer dalam instansi agar lebih dapat meningkatkan keterampilan dan ketelitian dalam bekerja agar kinerja lebih efektif sesuai dengan prosedur atas kegiatan operasional yang ada pada Dinas Kelautan dan Perikanan Provinsi Sumatera Utara.